2013
DOI: 10.1177/0300060513484435
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic response of facial nerve stimulation under different levels of neuromuscular blockade during middle-ear surgery

Abstract: Objective: To investigate facial nerve monitoring in patients receiving the partial nondepolarizing neuromuscular blocking agents (NMBAs), remifentanil and propofol. Methods: Patients with normal facial function and advanced middle-ear disease were enrolled. For total intravenous anaesthesia (TIVA), propofol and remifentanil were infused as induction/ maintenance anaesthesia. Stimulation thresholds and amplitudes were recorded at each train-offour (TOF) nerve stimulation level. Time differences between start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Greater doses of propofol, however, lead to a significant negative effect in the FNIM. 24,25 Classically, the administration of neuromuscular blocking agents is thought to be detrimental to intraoperative nerve monitoring, as they act directly in the neuromuscular junction. Choe et al 25 have showed, nonetheless, that during TIVA by combing propofol and remifentanil, the controlled use of nondepolarizing neuromuscular blocking agents would not hinder facial nerve monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater doses of propofol, however, lead to a significant negative effect in the FNIM. 24,25 Classically, the administration of neuromuscular blocking agents is thought to be detrimental to intraoperative nerve monitoring, as they act directly in the neuromuscular junction. Choe et al 25 have showed, nonetheless, that during TIVA by combing propofol and remifentanil, the controlled use of nondepolarizing neuromuscular blocking agents would not hinder facial nerve monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Classically, the administration of neuromuscular blocking agents is thought to be detrimental to intraoperative nerve monitoring, as they act directly in the neuromuscular junction. Choe et al 25 have showed, nonetheless, that during TIVA by combing propofol and remifentanil, the controlled use of nondepolarizing neuromuscular blocking agents would not hinder facial nerve monitoring. 24 Halogenated volatile compounds might completely abolish neuroelectrophysiological responses, and are, therefore, not routinely used when intraoperative nerve monitoring is considered during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…a train-offour count of 3 or 4) does not appear to affect the ability of the facial nerve monitor to function. 13 An alternative option is to avoid neuromuscular blockade entirely; however, neuromuscular blockade-free intubation techniques in adults can increase the risk of haemodynamic instability, poor intubating conditions, and postoperative airway discomfort. 14 Nitrous oxide is typically avoided because of its ability to diffuse into the non-compliant middle ear cavity faster than nitrogen diffuses out.…”
Section: General Anaesthetic Techniquesmentioning
confidence: 99%